Dietary taurine supplementation decreases fat synthesis by suppressing the liver X receptor α pathway and alleviates lipid accumulation in the liver of chronic heat‐stressed broilers. (4th July 2019) - Lu, Zhuang; He, Xiaofang; Ma, Bingbing; Zhang, Lin; Li, Jiaolong; Jiang, Yun; Zhou, Guanghong; Gao, Feng
Abstract: BACKGROUND: Chronic heat stress can enhance fat synthesis and result in lipid accumulation in the liver of broilers. To investigate the effects and molecular mechanisms of dietary taurine supplementation on fat synthesis and lipid accumulation in the liver of chronic heat‐stressed broilers, 144 28 day‐old chickens (Arbor Acres) were randomly distributed to normal control (NC, 22 °C, basal diet), heat stress (HS, consistent 32 °C, basal diet), or heat stress plus taurine (HS + T, consistent 32 °C, basal diet +5.00 g kg −1 taurine) groups for a 14‐day feeding trial. RESULTS: Compared with those of the HS group, dietary taurine supplementation significantly decreased the level of very‐low‐density lipoprotein and the activity of aspartate aminotransferase in plasma and the relative weight of liver in the HS + T group. In addition, dietary taurine supplementation also significantly decreased the levels of triglyceride, acyl‐CoA carboxylase (ACC) and fatty acid synthase (FAS), and suppressed the mRNA expression levels of liver X receptor α (LXRα), sterol response element‐binding protein 1c, ACC and FAS in the liver of chronic heat‐stressed broilers. Meanwhile, dietary taurine supplementation effectively alleviated lipid accumulation in the liver of broilers exposed to chronic heat stress. CONCLUSION: Chronic heat stress significantly increased fat synthesis and resulted in excess lipid deposition in the liver of broilers. Dietary taurine supplementation can effectively decrease fat synthesis by suppressing the LXRα pathway and alleviate lipid accumulation in the liver of chronic heat‐stressed broilers. © 2019 Society of Chemical Industry